Correction Notice for "Letter from the Editors" (WSFH, Vol. 50) (Journal of the Western Society for French History)
In the "Letter from the Editors" for this issue (Journal of Western Society for French History (WSFH), 2024, Vol. 50, DOI 10.3998/wsfh.7119) an acknowledgment paragraph was mistakenly omitted at the time of publication. The editors regret this error. As of February 2025, the acknowledgment has been added to the published article. It reads, "The editors would like to acknowledge Editorial Assistant Keith Donaldson for his invaluable assistance with this issue. Funding for Keith's position was made possible through the Serial Event Publications Fund at Simon Fraser University."